2002
DOI: 10.1051/rnd:2002030
|View full text |Cite
|
Sign up to set email alerts
|

Small intestine growth and morphometry in piglets weaned at 7 days of age. Effects of level of energy intake

Abstract: -Two trials involving a total of 56 pigs were conducted to examine the effects of weaning at 7 d of age (trial 1) and of energy intake level and length of post-weaning underfeeding period (trial 2) on small intestinal (SI) development and morphometry. At 3 d after weaning, weight of the SI and mucosa (g/kg body weight) and villous height along SI were reduced by 20, 36 and 41%, respectively, compared to the day of weaning. Intestinal morphometrical changes are dependent on SI site and days post-weaning. Villou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 42 publications
6
45
1
10
Order By: Relevance
“…Low energy intake at weaning is the most important factor affecting small intestine villous height of piglets after weaning (Marion et al, 2002), and has known negative effects on the piglets' metabolism, growth and health (Le Dividich and Sè ve, 2000;Dong and Pluske, 2007), thus being a major welfare issue. The distress associated with the separation from the sow and the inexperience with ingestion of solid feed at this age possibly underlie the low feeding behaviour during the first days after weaning, with a stronger effect on the youngest group.…”
Section: Discussionmentioning
confidence: 99%
“…Low energy intake at weaning is the most important factor affecting small intestine villous height of piglets after weaning (Marion et al, 2002), and has known negative effects on the piglets' metabolism, growth and health (Le Dividich and Sè ve, 2000;Dong and Pluske, 2007), thus being a major welfare issue. The distress associated with the separation from the sow and the inexperience with ingestion of solid feed at this age possibly underlie the low feeding behaviour during the first days after weaning, with a stronger effect on the youngest group.…”
Section: Discussionmentioning
confidence: 99%
“…So, we did not exclude that structural alterations might have occurred earlier. Indeed, Marion et al, (2002) showed that after weaning villous atrophy was first noticed in the proximal part of the small intestine. The restoration of the upper part of intestinal mucosa architecture was then noticed at the same time that villous atrophy concerns the distal part.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated descriptive parameters of intestine, both structural, such as weight parameters and morphology, and functional, such as mucosal enzyme activities. Modifications of these criteria were previously found to be associated with developmental alteration, for example, at weaning (Marion et al, 2002;Montagne et al, 2007) or in total parenteral feeding (Goldstein et al, 1985;Adeola et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Samples were micro-dissected under binocular optical. According to the technique of Goodlad et al [10], villi and crypt sizes were measured as reported [11].…”
Section: Structural Analysesmentioning
confidence: 99%